Quercetin ameliorates glucose and lipid metabolism and improves antioxidant status in postnatally monosodium glutamate-induced metabolic alterations - Seiva, Fabio R. F. [UNESP]; Chuffa, Luiz Gustavo A. [UNESP]; Braga, Camila Pereira [UNESP]; Amorim, Joao Paulo A.; Fernandes, Ana Angelica H. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
We reported the effects of quercetin on metabolic and hormonal profile as well as serum antioxidant activities in a model of MSG (monosodium glutamate)-induced obesity. Rats were divided into 4 groups: MSG group, submitted to neonatal treatment with high doses of MSG, administrated subcutaneously during 10 days, from 2 day-old; control groups, which received the same volume of saline. After completing 30 day-old, these groups were subdivided into 4 groups: control and MSG groups treated and non-treated with quercetin at doses of 75 mg/kg body weight (i.p.) over 42 days. BW gain and food consumption were higher in MSG treated rats and quercetin significantly reduced BW by 25%. While MSG increased triacylglycerol, total cholesterol and fractions, and reduced HDL concentrations, administration of quercetin normalized HDL-cholesterol and reduced others lipids. Insulin, leptin, glucose and creatinine levels were raised in MSG-treated rats and reduced after quercetin treatment. Alanine transaminase, aspartate transaminase, lactate dehydrogenase and alkaline phosphatase activities were lower after MSG-quercetin combination compared to rats given only MSG. MSG-quercetin combination augmented total protein and urea levels as well as glutathione peroxidase and superoxide dismutase activities in contrast to MSG-treated animals. Quercetin normalized serum lipid and glucose profile and minimized the MSG-related toxic effects, which was associated to its antioxidant properties. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Monosodium glutamate; Lipid profile; Metabolism; Quercetin; Hepatoprotection; Antioxidant defenses